Snøens formler Et naturfenomen i litteraturen - Seiler, Thomas (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
In her well-known song, 'Når himmelen faller ned' ('When the Sky Falls Down'), the Norwegian musician Anne Grete Preus described snow as 'celestial tipp-ex' and a mighty 'wonder'. But what exactly is it that snow corrects? And what gives snow its power? Snow's Formulas: A Natural Phenomenon in Literature attempts to answer these and similar questions by discussing the motif of snow in the context of modernization processes marked by increasing instrumentalization and rationalization. Snow transforms landscapes and defies modernity's innovations; it simultaneously obscures and accentuates, and also enchants. This process can be described in different ways: as the sublime's breakthrough in a philosophical, aesthetic sense, or, in a poetological sense, as non-mimetic writing. This strategy plays out in language, and the objective of this study has been to investigate snow's rhetoricity and how literary depictions of snow can be in response to the challenges of modernity. The book includes readings of texts by H.C. Andersen, Olaf Bull, Hans Børli, Paul Celan, Alexander Kielland, Jonas Lie, Tor Ulven and Tarjei Vesaas, among others. The relationship between snow and modernity is illustrated from a dual perspective. Emphasis is placed on the individual's position and self-perception within the process of modernization, as well as on the aesthetical problems that arise when writing about snow. Snow makes a white surface; it 'overwrites' the ground and encourages a non-mimetic poetry. Snow can be said to be an engine of modern aesthetics that does not take language's referential aspect for granted.